TEKANAN AKADEMIK DAN DOOM SPENDING SEBAGAI BENTUK KOPING MALADAKTIF MAHASISWA - Nurul Fadhilah Desmi; M Fahli Zatrahadi; Miftahuddin (Counseling Milenial (CM), 2026)
Academic pressure is one of the common challenges experienced by university students during their academic life. This condition may affect students’ psychological well-being and encourage the emergence of various coping behaviors, including doom spending. This study aimed to describe the levels of academic pressure and doom spending behavior among students of the Economic Education Study Program at Sultan Syarif Kasim State Islamic University of Riau. The study employed a quantitative approach with a descriptive method. The sample was selected using purposive sampling and consisted of active students of the Economic Education Study Program. Data were collected through questionnaires measuring academic pressure and doom spending behavior. Data were analyzed using descriptive statistics by calculating mean scores to determine the category of each variable.The findings revealed that the level of academic pressure was in the moderate category with a mean score of 3.00. Meanwhile, doom spending behavior was also categorized as moderate with a mean score of 2.33. These results indicate that students experience a considerable level of academic demands and that some students tend to engage in impulsive spending as a response to certain emotional conditions. Therefore, strengthening guidance and counseling services, stress management programs, and financial literacy education is necessary to help students cope with academic pressure more adaptively and reduce excessive consumptive behavior.